Once we have determined that the matrix is invertible, the next step is to find the inverse. The inverse of a 2x2 matrix is found using a specific formula: \(\begin{bmatrix} a & b \ c & d \end{bmatrix}^{-1} = \frac{1}{ad - bc}\begin{bmatrix} d & -b \ -c & a \end{bmatrix} \).
Applying this to our matrix \(\begin{bmatrix}-4 & 1 \ 6 & -2 \end{bmatrix}\), we substitute the values:
- \(a = -4\)
- \(b = 1\)
- \(c = 6\)
- \(d = -2\)
Using the previously calculated determinant 2, we have:
\(\frac{1}{2}\begin{bmatrix}-2 & -1 \ -6 & -4 \end{bmatrix} \).
Simplifying each term inside the matrix, we finally get: \(\begin{bmatrix}-1 & -\frac{1}{2} \ -3 & -2 \end{bmatrix} \).
This is the inverse of the given 2x2 matrix.